Transforming Growth Factor Beta1 in Porcine Seminal Plasma on Characteristic of Sperm and Reproductive Efficiency in Sows - Tongrueng, Surapong; Vongpralub, Thevin; Srimooltho, Watcharaporn; Phasuk, Yupin (Science & Technology Asia, 2021)
Transforming growth factor-β1(TGF-β1) in porcine seminal plasma (SP) and TGF-β1 concentrations under different storage periods at 16°C were investigated. The effects of adding TGF-β1, to boar semen, on sperm characteristics and reproductive performance in sows were also examined. TGF-β1 in boar SP was measured by enzyme-linked immunosorbent assay (ELISA) technique. Mean concentrations of TGF-β1 in individual ejaculated SP samples demonstrated a wide variation at 8.94-588.24 pg/mL with a decrease in concentration of 46.10±5.52% after 72 hours. The supplementation of TGF-β1 to fresh semen at 0, 1000, and 2000 pg/100 mL was performed in order to evaluate its effect on sperm characteristics. Results showed a significant difference at 24 hours in the following characteristics: viability, progressive, and acrosome integrity, viability, velocity average path (VAP), and velocity curvilinear (VCL) at 72 hours (P<0.05). Acrosome integrity, mitochondrial function, motility, velocity average path (VAP), velocity straight line (VSL), and velocity curvilinear (VCL) were not significantly difference at 24 hours (P>0.05). Mitochondrial function, progressive motility, and VSL were not significantly different at 72 hours (P>0.05). In addition, the supplementation of TGF-β1 at 0, 500, and 1000 pg/100 mL of fresh boar semen for artificial insemination in sows did not result in a significant difference in conception rate, farrowing rate, litter size, or total born alive (P>0.05).